Sistem Informasi Pemesanan Menu Makanan dan Minuman Berbasis Web Sebagai Penentu Nilai Menu Terbaik - John Adler; Raman Dika (Majalah Ilmiah UNIKOM, 2022)
Cafe is a place of business that is used to gather, relax or fill spare time, besides that the cafe also provides food and drinks. Ordering is one of the activities carried out by customers or buyers. In general, some cafe entrepreneurs have problems serving customers for ordering food and beverage menus, the problem is that customers have to wait a long time to place an order which is fast and practical, because buyers have to write in advance on paper so it takes a long time to place an order. Therefore, to be able to realize customer satisfaction, the aim of the researcher is to design a food and beverage menu ordering system, and determine the best menu using the TOPSIS method. TOPSIS method is a method that can be used to help solve a problem in determining the best menus based on ranking with predetermined criteria and alternatives. This system is designed using MySQL database, Bootstrap Framework and Codeigniter. With the information system ordering the food and beverage menu, it can assist in recording sales at the Solmed Meatball cafe, so that the data is organized and stored properly. The results of the research, it can be seen that the ranking of the buyer's best menu assessment is the first ranking of Indomie meatballs, the second is good day drinks, the third is empty pedal meatballs, the fourth is empty meatballs. Then the impact of this research is that it can help in the process of ordering food and drink menus online at the Baskso Solmed Pakde Slamet cafe, and can assist in determining the best menus based on criteria and alternative values. Key Words : information system, website, cafe, menu ordering, TOPSIS